Barrientosiimonas humi for medical use - Cheah, Yoke Kqueen; Khoo, Chai Hoon; Chu, Pek Lim (2014)
The present invention relates to Barrientosiimonas humi, parts of Barrientosiimonas humi, and/or extracts of Barrientosiimonas humi for use as medicament, more particularly for use in a method of treatment of cancer and bacterial infections, or as a disinfectant.